New threats of genetic research in sport - Cieszczyk, P.; Maciejewska, A.; Sawczuk, M (Journal of Human Sport & Exercise, 2010)
The main goal of this paper is to show the main threats and ethical controversies associated with the application of molecular biology in sport. Such ethical reservations are presently the most important obstacle to wider application of genetics in training and only a small fraction of its remarkable potential is used in sport practice. However, the increasing availability of molecular research and associated possibilities create a situation where the moral questions need to be comprehensively addressed.